Comparison of MRI Osteoarthritis Knee Score with Clinico-Radiological Grading - Amul M. Halmandge; Rajesh Malik; Radha Sarawagi; Jitendra Sharma (Indian Journal of Radiology and Imaging, 2025)
Background Knee joint osteoarthritis (OA) is among the most prevalent degenerative diseases of the joints in the body. Various scoring system exists for grading OA, such as (1) magnetic resonance imaging (MRI) Osteoarthritis Knee Score (MOAKS), (2) clinical grading by Western Ontario and McMaster Universities Arthritis Index (WOMAC), and (3) X-ray grading of the Kellgren–Lawrence grading system (K-L).